A comparative analysis on the need to regulate the law on allocating air marshal on-board Malaysia’s aircraft / Muhammad Amry Abdul Hapiz … [et al.] - Abdul Hapiz, Muhammad Amry; Mohd Aris, Nur Nabilah; Rahmat, Siti Nur Aisyah; Zamri, Zahia Adlina (Faculty of Law, 2014)
The aim of this research is to ascertain the applicability of air marshal in helping to supplement the Malaysian airline system. The existing security system is full of weaknesses, contributing to the rise of undesirable events such as plane disappearance and hijacking. The widespread belief on the existing security measure has managed to only instil temporary confidence in the security system among the public. Thus, this paper demonstrates that the application of air marshal promotes a better sense of security, allowing passengers of local airlines to feel safe on-board air crafts. This paper also reviewed the operation of air marshal teams in the United States of America and Israel and the success that they had accomplished through the deployment of air marshal. Interviews with the Principal Assistant Director (Airlines and Catering) of the Department of Civil Aviation, the President of National Union of Flight Attendants Malaysia and a pilot from Malaysia Airlines had been conducted to explore the suitability of air marshal program to be incorporated into the Malaysian aviation system. The general result is that the air marshal could be positioned in the system, but not without consistent effort as the road to implement it will be shackled with many limitations, principally the lack of awareness from the authority about the advantages of air marshal. The authors of the research believe that the application of air marshal program is feasible as it will not only enhance the current civil aviation system, but simply supplements it in order to avoid future mishaps.